2018
DOI: 10.1186/s13017-018-0217-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Change in Functional Outcome at six months and twelve months after Severe Injury: A Retrospective Cohort Study

Abstract: BackgroundThere is increasing focus on long-term survival, function and quality-of-life for trauma patients. There are few studies tracking longitudinal changes in functional outcome over time. The goal of our study was to compare the Glasgow Outcome Scale-Extended (GOSE) at 6 months and 12 months in blunt trauma survivors with an Injury Severity Score (ISS) of more than 15.MethodsUsing the Singapore National Trauma Registry 2011–2013, patients with 6-month GOSE and 12-month GOSE scores were analysed. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
3
1
0
1
Order By: Relevance
“…Of interest, our study also showed that better physical and mental well-being, measured by the SF-12 were associated with increased improvements in pain over time, which concurs with research showing that an inability to exercise and depressing can exacerbate pain [39]. Overall, better physical and mental well-being are associated with higher functioning over time [33,35]. This reinforces the need for easy access to cost-neutral or low cost rehabilitation programs as part of the comprehensive discharge plan to improve physical and mental health outcomes [38].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Of interest, our study also showed that better physical and mental well-being, measured by the SF-12 were associated with increased improvements in pain over time, which concurs with research showing that an inability to exercise and depressing can exacerbate pain [39]. Overall, better physical and mental well-being are associated with higher functioning over time [33,35]. This reinforces the need for easy access to cost-neutral or low cost rehabilitation programs as part of the comprehensive discharge plan to improve physical and mental health outcomes [38].…”
Section: Discussionsupporting
confidence: 88%
“…A middle-aged person may have more difficulty securing a job when they have recovered from their injury as either employers may have found alternative employees or the physically demanding nature of certain jobs may make finding employment more difficult for older people [33]. Consistent with other research [33][34][35] this study found lower functional status among those aged over 55 years, and those with a higher ISS. This could be due to natural physical decline related to advancing age, which impacts on recovery time [36].…”
Section: Discussionsupporting
confidence: 84%
“…This highlights the urgent need for interventions that initiate and extend a continuity of longterm engagement with tools like mobile health monitoring. Similar to the limited corpus of research on long-term outcomes after trauma, we found that many patients in this pilot study continued to express signs and symptoms of poor recovery and chronic injury sequalae months and years after their hospitalization (13,15,(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 75%
“…Auch der prätraumatische physische und psychische Zustand hat erheblichen Einfluss auf den funktionellen Outcome. Begleiterkrankungen und BMI beeinflussen nicht nur die Überlebensrate der Traumapatienten, sondern auch deren Lebensqualität [26,27]. Prognostische Einflüsse können in Relation zum Unfallzeitpunkt in prätraumatische, traumabedingte oder posttraumatische Faktoren eingeteilt werden (.…”
Section: Einflussfaktoren Auf Die Unfallfolgenunclassified